Crosstalk Between Trophoblast and Macrophage at the Maternal-Fetal Interface: Current Status and Future Perspectives - Ding, Jinli; Zhang, Yan; Cai, Xiaopeng; Diao, Lianghui; Yang, Chaogang; Yang, Jing (Frontiers in Immunology, 2021)
The immune tolerance microenvironment is crucial for the establishment and maintenance of pregnancy at the maternal-fetal interface. The maternal-fetal interface is a complex system containing various cells, including lymphocytes, decidual stromal cells, and trophoblasts. Macrophages are the second-largest leukocytes at the maternal-fetal interface, which has been demonstrated to play essential roles in remodeling spiral arteries, maintaining maternal-fetal immune tolerance, and regulating trophoblast's biological behaviors. Many researchers, including us, have conducted a series of studies on the crosstalk between macrophages and trophoblasts at the maternal-fetal interface: on the one hand, macrophages can affect the invasion and migration of trophoblasts; on the other hand, trophoblasts can regulate macrophage polarization and influence the state of the maternal-fetal immune microenvironment. In this review, we systemically introduce the functions of macrophages and trophoblasts and the cell-cell interaction between them for the establishment and maintenance of pregnancy. Advances in this area will further accelerate the basic research and clinical translation of reproductive medicine.